Crystallization and preliminary crystallographic studies of the complement 1qA globular domain from zebrafish, Dare‐C1qAgD. Issue 7 (1st July 2014) - Yuan, Hongyu; Chen, Rong; Liu, Yanjie; Tariq, Mansoor; Sun, Yaping; Xia, Chun
<x xml:space="preserve">Abstract</x> Complement 1q (C1q) is the first component of the complement system which can initiate the classical complement pathway. In human, C1q is composed of 18 polypeptide chains: six C1qA chains, six C1qB chains and six C1qC chains. Each chain has a signal peptide and is comprised of a collagen‐like region and a C‐terminal C1q globular domain (C1qgD), which is organized as a heterotrimer. C1qgD can recognize antigen–antibody complexes containing IgG and IgM or can bind directly to the C‐reactive protein. Although the classical complement pathway is found from fish to mammals, only the human C1qgD structure has been determined. Compared with that of mammals, fish C1q exhibits similar immune functions and genome arrangement. In order to illustrate the structure of C1qgD in fish, zebrafish (Danio rerio) C1qA globular domain (Dare‐C1qAgD) was expressed, purified and crystallized. X‐ray diffraction data were collected from a crystal to a resolution of 2.05 Å; the crystal belonged to the orthorhombic space group P212121, with unit‐cell parameters a = 50.347, b = 85.059, c = 95.560 Å. It contained three molecules in the asymmetric unit. The Matthews coefficient value VM was 2.31 Å3 Da−1, with a calculated solvent content of 46.7%. The data will help to give insight into the structural basis of C1qA in fish species.